Hexokinase 2 dimerization and interaction with voltage‐dependent anion channel promoted resistance to cell apoptosis induced by gemcitabine in pancreatic cancer. (19th August 2019) - Fan, Kun; Fan, Zhiyao; Cheng, He; Huang, Qiuyi; Yang, Chao; Jin, Kaizhou; Luo, Guopei; Yu, Xianjun; Liu, Chen
Abstract: Gemcitabine (GEM) is the standard chemotherapy drug for pancreatic cancer. Because of widespread drug resistance, the effect is limited. Therefore, it is urgent to reveal the underlying mechanism. Glycolysis is the most remarkable character of tumor aberrant metabolism, which plays vital roles on tumor drug resistance. Hexokinase 2 (HK2), as the key enzyme regulating the first‐step reaction of glycolysis, is overexpressed in many kinds of tumors. The putative role of HK2 resisting GEM therapy was investigated in this study. We found that HK2 was overexpressed in pancreatic cancer and associated with poor prognosis. HK2 knockdown decreased pancreatic cancer cell proliferation, migration viability, and promoted cell apoptosis in vitro. HK2 high expression in pancreatic cancer showed GEM resistance. HK2 knockdown increased the sensitivity of pancreatic cancer cell to GEM, the growth of xenograft tumor with HK2 knockdown was also further decreased with the GEM treatment compared with control in vivo. GEM‐resistant pancreatic cancer showed the increase of HK2 dimer rather than HK2 mRNA or protein. Our study revealed that the ROS derived from GEM promoted HK2 dimerization combining with voltage‐dependent anion channel, which resulted in the resistance to GEM. Meanwhile, our study established a new sight for GEM resistance in pancreatic cancer. Abstract : Hexokinase 2 (HK2) overexpression promoted pancreatic cancer growth and gemcitabine (GEM) resistance. ROS mediated the HK2 dimerization induced by GEM.